The awareness of low sexual desire in female among married women in Indonesia: a preliminary study - Jivitha Munusamy; I Made Oka Negara (DiscoverSys Inc., 2021)
Background: Sexual dysfunction is difficulty experienced by any individual or a couple during any stage of normal sexual activity. Sexual dysfunction occurs among men and also women. This study aims to identify the level of awareness, knowledge, and attitude of married women towards hypoactive sexual desire disorder in their life.Methods: A cross-sectional descriptive study was conducted among 75 married women using a self-administered questionnaire through social media platforms to ensure easy accessibility to a wider participant. This study's inclusion criteria are married women from the age of 20-40 years old who volunteer themselves and take place in the survey. Factors that influence low sexual desire in married women, such as age, social life, hypoactive sexual desire, and the level of communications or understanding among their partners, are assessed in this study. Data were analyzed using SPSS version 20 for Windows.Results: From the total of 75 participants, a total of 56.00% haven't heard or came across the term low sexual desire in their life. Meanwhile, a total of have 32.00% came across this term. The survey shows that participants who have participated in this survey have a higher morbidity rate on pregnancy history with complications that represent 59.00% of them. Meanwhile, participants with a history of pregnancy without complications consist of 41.00%.Conclusion: There is still a more significant number of women still unaware of hypoactive sexual desire disorder. Most of them think that hypoactive sexual desire disorder is common.